Sex-Specific Differences in Related Indicators of Blood Pressure in School-Age Children With Overweight and Obesity: A Cross-Sectional Study - He, Hongmei; Yang, Shujun; Qiu, Na; Qiao, Ling; Ding, Yong; Luo, Jiajia; Li, Yuan; Luo, Zengyou; Huang, Yingsa; Pang, Huishen; Ji, Shaoping; Zhang, Lu; et al. (Frontiers in Pediatrics, 2021)
Abstract Objective: The objective of this study is to further explore the difference between elevated blood pressure (EBP), elevated pulse pressure (EPP) and elevated mean arterial pressure (EMAP) and obesity in Chinese school-age children by sex. Methods: We performed a cross-sectional study of 935 children between seven and twelve years old. Overweight and obesity were defined by body mass index and body composition. The multivariate logistic regression and the adjusted population attributable risk were used to assess the effects of obesity on pre-EBP/EBP, EPP and EMAP. The interactions were used to identify the modification of obese on the relationship between related indicators of blood pressure and height or age. Results: The average age of the children included in the study was 10. Boys with overweight and obesity had higher pre-EBP/EBP, EPP and EMAP (P<0.05). The multivariate logistic regression analysis showed that overweight and obesity had a greater impact on BP and MAP than PP, especially in boys [Odds ratio (OR)>1]. pre-EBP/EBP in 79% of boys and 76% of girls could be attributable to the visceral fat level. The interaction between BP, PP, MAP and height or age was modestly increased in children with overweight and obesity, especially in boys. Conclusions: Independent of age and height, obesity not only increases blood pressure, it also increases mean arterial pressure and pulse pressure, and this effect is more pronounced in boys.